1995
DOI: 10.1177/104063879500700308
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Outbreaks ofClostridium Difficile-Associated Diarrhea in Horses in a Veterinary Medical Teaching Hospital

Abstract: Abstract.Intestinal colonization with toxigenic strains of Clostridium difficile was documented in 9 of 10 horses with acute onset diarrhea in a veterinary medical teaching hospital, whereas a similar isolate was detected in only 1 of 23 other horses without diarrhea in the hospital. One horse with diarrhea was infected simultaneously with both C. difficile and Salmonella krefeld. Clostridium difficile was detected by fecal culture on selective medium, confirmed with a latex particle agglutination test, and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 21 publications
(2 reference statements)
1
71
0
2
Order By: Relevance
“…C. difficile spores are comparatively resistant to common disinfectants making C. difficile a lasting environmental contaminant. Many studies have reported a strong association between nosocomial C. difficile infection and antibiotic therapy in horses (Madewell et al, 1995;Ruby et al, 2009;Barr et al, 2013). In a Prospective study conducted in horses pre-treated with penicillin followed by experimental infection resulted in increased isolation of C. difficile from faecal samples, revealing the role of antimicrobials as a risk factor (Gustafsson et al, 2004).…”
Section: Clostridium Difficilementioning
confidence: 99%
See 1 more Smart Citation
“…C. difficile spores are comparatively resistant to common disinfectants making C. difficile a lasting environmental contaminant. Many studies have reported a strong association between nosocomial C. difficile infection and antibiotic therapy in horses (Madewell et al, 1995;Ruby et al, 2009;Barr et al, 2013). In a Prospective study conducted in horses pre-treated with penicillin followed by experimental infection resulted in increased isolation of C. difficile from faecal samples, revealing the role of antimicrobials as a risk factor (Gustafsson et al, 2004).…”
Section: Clostridium Difficilementioning
confidence: 99%
“…Prevalence studies have shown that 4-9% patients endure from a nosocomial infection (Mielke, 2010). The occurrence of nosocomial infections in veterinary hospitals has not been well established and in nascent stage (Boerlin et al, 2001;Johnson, 2002;Morley, 2004;Smith, 2004;Traub-Dargatz et al, 2004;Morley and Weese, 2008), even though the nosocomial infections are of immense significance in the field of veterinary medicine since quite a lot of March 2015 | Volume 3 | Special issue 2 | Page 2 nosocomial outbreaks of different etiologies in veterinary hospitals has been documented (Castor et al, 1989;Madewell et al, 1995;Hartmann et al, 1996;Konkle et al, 1997;Tillotson et al, 1997;Seguin et al, 1999;Weese and Armstrong, 2003;Cherry et al, 2004;Wright et al, 2005;Weese et al, 2006a;Dallap et al, 2010;Goehring et al, 2010;Steneroden et al, 2010). Six of those outbreaks had evidence of zoonotic infection (Konkle et al, 1997;Seguin et al, 1999;Cherry et al, 2004;Wright et al, 2005;Weese et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…6 The rate of C. difficile isolation from horses with diarrhea varies from 12.7 to 90% of adults, and 16.7 to 63% of foals. 71,92,159 However, the highest culture rates were associated with CDAD outbreaks and might not accurately reflect the rate in all cases of equine diarrhea. Of all equine diarrhea cases at one veterinary teaching hospital, 20-25% were attributed to C. difficile.…”
Section: 2867mentioning
confidence: 99%
“…7 Clostridium difficile-associated diarrhea of variable severity occurs sporadically and epidemically in adult horses. It is often antibiotic associated or nosocomial, 6,7,18 and the role of the organism in its etiology has been confirmed via a prospective study. Clostridium difficile was isolated from .12% of horses with colitis but from only 0.4% of normal adults.…”
mentioning
confidence: 99%